Convergent close coupling versus the generalized Sturmian function approach: Wave-function analysis - Ambrosio, Marcelo José (2015)
We compare the physical information contained in the Temkin-Poet (TP) scattering wave function representing electron-impact ionization of hydrogen, calculated by the convergent close-coupling (CCC) and generalized Sturmian function (GSF) methodologies. The idea is to show that the ionization cross section can be extracted from the wave functions themselves. Using two different procedures based on hyperspherical Sturmian functions we show that the transition amplitudes contained in both GSF and CCC scattering functions lead to similar single-differential cross sections. The single-continuum channels were also a subject of the present studies, and we show that the elastic and excitation amplitudes are essentially the same as well.